Prevalence of vitamin B12 depletion and deficiency in Liechtenstein. Issue 2 (14th December 2012) - Koenig, Victoria; Stanga, Zeno; Zerlauth, Manfred; Bernasconi, Luca; Risch, Martin; Huber, Andreas; Risch, Lorenz
Abstract Objective Data about vitamin B12 (B12) deficiency in the general population are scarce. The present study was performed to determine the prevalence of B12 deficiency in the general population of the Principality of Liechtenstein, as well as to identify sub-populations potentially at high risk. Design Retrospective study. Setting Ambulatory setting, population of the Principality of Liechtenstein. Subjects Seven thousand four hundred and twenty-four patients seeking medical attention whose serum samples were referred for routine work-up in an ambulatory setting were consecutively enrolled. Serum total B12 was determined in all patients in this cohort. In addition, for a subgroup of 1328 patients, serum holotranscobalamin was also measured. Prevalence of B12 deficiency was calculated. Further, multivariate logistical regression models were applied to identify covariates independently associated with B12 deficiency and depletion. Results Nearly 8 % of the general population was suffering from either B12 depletion or deficiency. The ratio between B12 depletion and deficiency was 2:1 for all age ranges. Pathological changes were detected predominantly in older people. Female gender was a significant predictor of B12 depletion. In the cohort, nearly 40 % exhibited either depletion or deficiency of B12. Conclusions B12 depletion and deficiency are common in Liechtenstein, a Central European country. The measurement of biochemical markers represents a cost-efficient and valid assessment of the B12 state. When a deficiency of B12 is diagnosed at an early stage, many cases can be treated or prevented, with beneficial effects on individual outcomes and subsequent potential reductions in health-care costs.